Reduced Priming Effect for Visual–Spatial Perspective Taking in Patients With Severe Acquired Brain Injury. (24th August 2021) - Costa, Alberto; Bivona, Umberto; Sulpizio, Valentina; Nappo, Raffaele; Mastrilli, Ludovica; Formisano, Rita; Aloisi, Marta; Contrada, Marianna; Caltagirone, Carlo; Galati, Gaspare
Abstract: Objective: Social cognition can be impaired after a severe acquired brain injury (sABI), but mechanisms potentially underlying these difficulties remain to be clarified. This study aimed at investigating perspective taking ability in individuals with sABI. Method: Twenty individuals with sABI and 20 healthy controls (HCs) have been enrolled in this case–control study. All participants were submitted to an experimental visual–spatial priming memory procedure and a self-report assessment of perspective taking (i.e., the Interpersonal Reactivity Index [IRI]). Individuals with sABI were submitted to neuropsychological tests to assess executive subcomponents, working memory, and visual attention. Results: The analysis on self-report scales data documents a significant between groups difference in the IRI- Fantasy subscale, with HCs showing a higher tendency to imaginatively transpose oneself into fictional situations than individuals with sABI. Analysis of performance on the experimental procedure revealed the priming effect in HCs but not in sABI individuals. Moreover, individuals with sABI performed significantly poorer than HCs on the indices of the experimental procedure. Conclusions: Our data preliminarily demonstrated that visual–spatial perspective taking is reduced after sABI. Findings above could give some clues for the rehabilitative intervention in sABI and suggest the possible application of the procedure here used in assessing perspective taking after sABI.